2017
DOI: 10.1038/onc.2017.85
|View full text |Cite
|
Sign up to set email alerts
|

Interferon γ is a STAT1-dependent direct inducer of BCL6 expression in imatinib-treated chronic myeloid leukemia cells

Abstract: B-cell CLL/lymphoma 6 (BCL6) exerts oncogenic effects in several human hematopoietic malignancies including chronic myeloid leukemia (CML), where BCL6 expression was shown to be essential for CML stem cell survival and self-renewal during imatinib mesylate (IM) treatment. As several lines of evidence suggest that interferon γ (IFNγ) production in CML patients might have a central role in the response to tyrosine kinase inhibitor (TKI) therapy, we analyzed if IFNγ modulates BCL6 expression in CML cells. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…These data support a protumorigenic effect of IFN-γ in CML and suggest that IFN-γ may contribute to TKI resistance. Their data suggest that combining TKIs with inhibitors of BCL6 or MCL1 is a potential approach to eradicate CML stem cells ( 45 ).…”
Section: Type II Ifn (Ifn-γ)mentioning
confidence: 99%
“…These data support a protumorigenic effect of IFN-γ in CML and suggest that IFN-γ may contribute to TKI resistance. Their data suggest that combining TKIs with inhibitors of BCL6 or MCL1 is a potential approach to eradicate CML stem cells ( 45 ).…”
Section: Type II Ifn (Ifn-γ)mentioning
confidence: 99%
“…Signal transduction and transcriptional activator 1 (STAT1) is encoded by STAT1 gene in human being. Specific expression of STAT1 can be mediated by some cytokines, such as IFN-α ( 69 , 70 ), IFN-γ ( 71 , 72 ), or IL-6 ( 73 , 74 ). IFN-α binds receptor and triggers STAT signal via its phosphorylation and activation of STAT1 and STAT2.…”
Section: Pos Affect Mitogen-activated Protein Kinases (Mapk) Signalinmentioning
confidence: 99%
“…CML can be treated using a combination of these 11 genes. For example, studies have shown that the combination of TKIs with BCL6 and MCL1 inhibitors may lead to the complete eradication of CML stem cells (Madapura et al, ).…”
Section: Discussionmentioning
confidence: 99%